1993
DOI: 10.1038/366069a0
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous loss of T-cell tolerance to glutamic acid decarboxylase in murine insulin-dependent diabetes

Abstract: Insulin-dependent diabetes mellitus (IDDM) in non-obese diabetic (NOD) mice results from the T-lymphocyte-mediated destruction of the insulin-producing pancreatic beta-cells and serves as a model for human IDDM. Whereas a number of autoantibodies are associated with IDDM, it is unclear when and to what beta-cell antigens pathogenic T cells become activated during the disease process. We report here that a T-helper-1 (Th1) response to glutamate decarboxylase develops in NOD mice at the same time as the onset of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

25
600
6
7

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,038 publications
(642 citation statements)
references
References 27 publications
25
600
6
7
Order By: Relevance
“…We found that the production of IL-4 increased, whereas the production of IFN-γ decreased, indicating that the immunisation of NOD mice with rVV-GAD65 induced a Th2 immune response in an antigenspecific manner. Our finding is consistent with the results of previous reports on NOD mice treated with GAD protein systemically, nasally or orally [28,29,33,34,35] or vaccinated with GAD encoding plasmid DNA [41]. Th2 immune responses induced by rVV-GAD immunisation could play an important role in the prevention of autoimmune diabetes in this animal model.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that the production of IL-4 increased, whereas the production of IFN-γ decreased, indicating that the immunisation of NOD mice with rVV-GAD65 induced a Th2 immune response in an antigenspecific manner. Our finding is consistent with the results of previous reports on NOD mice treated with GAD protein systemically, nasally or orally [28,29,33,34,35] or vaccinated with GAD encoding plasmid DNA [41]. Th2 immune responses induced by rVV-GAD immunisation could play an important role in the prevention of autoimmune diabetes in this animal model.…”
Section: Discussionsupporting
confidence: 93%
“…In Type I diabetes, GAD and insulin have been identified as major autoantigens and tolerisation against these autoantigens has been attempted as a method for the prevention of the disease [14,32]. It has been reported that administration of purified GAD protein or peptide or insulin protein or peptide to NOD mice by a variety of routes can tolerise the T cell-mediated immune response against pancreatic beta cells, resulting in the prevention or delay of the development of insulitis and diabetes [28,29,33,34,35,36,37,38,39]. In many cases, the preventive effect was found to be associated with a Th2 shift [14,32].…”
Section: Discussionmentioning
confidence: 99%
“…With the onset of periinsulitis, beta-cell-antigenspecific T cells become detectable [25,32,33]. These islet-specific T cells are of TH1 phenotype and show signs of activation [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…These islet-specific T cells are of TH1 phenotype and show signs of activation [33,34]. Therefore, it seems that these T cells encounter their cognate antigen, get primed, expand clonally and acquire a TH1-phenotype as soon as periinsulitis develops.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple immune-related genes involving different biological functions, from antigen processing and presentation to T cell activation, migration and apoptosis, have been suggested as candidates for these Idd loci [17]. Nevertheless, several studies reported abnormal APC function in NOD mice, which might be related to the known T cell dysfunction in this strain [18][19][20].We previously identified a region within GAD65, p524-543 (p543), to which spontaneous T cell responses arise in young NOD mice as early as 3-4 weeks of life [1]. Interestingly, this 20mer peptide appeared to be comprised of two distinct determinants: an N-terminal moiety (p524-538 (p524)) and a C-terminal moiety (p530-543 (p530)).…”
mentioning
confidence: 99%